Дослідження можливостей використання випадкових сигналів в задачах пошуку пристроїв несанкціонованого знімання інформації - Загута, Є. А.; Горелов, Д. Ю. (ХНУРЕ, 2022)
The purpose of thesis is theoretical study of the structure of the response of a nonlinear diffuser under the action of random RF signal of a nonlinear radar to ensure the effective identification of the latter.